KEANEKARAGAMAN ARHTROPODA TANAH DAN KUALITAS TANAH PADA LAHAN TUMPANG SARI DI DESA SUKAWANGI KABUPATEN SUMEDANG - Hana Nurul Rahiim, Fathya
Intercropping system is a multicultural agrosystem with two or more different plants during one planting season. Intercropping systems can help the farmer to use the land efficiently and minimize crop failure. The physical, chemical, and biological conditions of the soil can change overtime. This research aims to study the fluctuation of the physical and chemical condition along with the arthropods community of intercropping agrosystem at Desa Sukawangi, Kabupaten Sumedang. Vegetations planted on the agrosystem are maize (Zea mays), common bean (Phaseolus vulgaris), and sweet potato (Ipomoea batatas). Data collection was held from August to October 2020 with two weeks gap from one period to another. Soil pH and soil moisture were measured using a soil tester. Soil nutrients analysis was organized at a soil laboratory in Balai Penelitian Tanaman Sayuran Lembang and interpreted according to a guide from Kementerian Pertanian (2009). Analysis of the arthropods community was held using a pitfall trap sampling method. pH measurement result showed no significant differences among all data, with pH of 5.6 to 7. Soil moisture measured in August was below 30% and tended to rise as the rainy season came in September and October. The result of the nutrient analysis showed a medium level for organic carbon, total nitrogen, calcium cation, boron, and CEC; a high for available potassium, magnesium cation, nitrate, and ammonium ion; and a very high for total potassium and phosphorus. 28 morphospecies were obtained from 9 different orders, 11 species were present at all periods. Species with the highest abundance were Tenebrionidae, Formicidae 1, Formicidae 2, Formicidae 3, and Formicidae 4 that composed of almost 90% of the average relative abundance. The community of soil arthropods showed a diversity index between 1.5-1.9, dominance index between 0.2-0.3, and evenness index between 0.5-0.7. Based on the soil nutrient analysis, along with physical and chemical conditions, the soil of the intercropping land is in a good condition. The abundance and diversity of soil biota were suspected to have a strong correlation with organic material input, pesticide application, and the intensity of physical soil transformation.